Flow settlement law of gangue paste-like filling slurry in room-and-pillar goaf - Xiaoping SHAO; Chuang TIAN; Lang LIU; Renlong TANG; Longqing LI; Mingan DUAN; Lei WANG (Meitan kexue jishu)
The development process of Yushenfu mining area has formed a large range of room and pillar goaf, resulting in a large area of suspended roof area. After a long period of natural weathering and creep, the support strength of the coal pillar in the hanging roof area is weakened, and there is a risk of instability and failure, and even a mine earthquake disaster. Based on the background of the treatment of the hanging roof area of the room-and-pillar goaf in a mine in Yushenfu mining area, this paper studies the flow and settlement law of the gangue paste-like slurry in the room-and-pillar goaf by building a room-and-pillar goaf simulation test platform based on the similarity theory. The study shows that after the filling, a natural slope of about 5° from the inlet to the exhaust hole is formed on the surface of the filling body; The filling rate near the inlet is the highest, and the filling rate decreases with the increase of flow distance. The ultrasonic wave velocity in the middle and lower parts of the slurry increases with time, while the upper part decreases first and then increases slowly. The slurry has better static anti-segregation performance as a whole; the proportion of coarse (fine) particle size gradually decreases (increases) along the flow direction, and the proportion of particle size near the vent side between adjacent coal pillars is slightly higher. The proportion of coarse (fine) particle size in the lower part is relatively large (small), and the proportion of coarse (fine) particle size in the upper part is relatively small (large); the strength of the filling sample shows a wave-like variation along the flow direction. The strength near the vent side is higher, and the strength of the filling sample increases with depth. The macroscopic defects of the filling sample are related to the fact that the bubbles generated inside the slurry cannot be discharged smoothly. Through this study, the flow and settlement law of filling slurry in room and pillar goaf is revealed, which can provide reference for the treatment of goaf and the elimination of hidden danger of large area suspended roof in similar mines in Yushenfu mining area.